Internalization of Multicultural Values through the Education Process in Manado State University - Umar, Mardan; Tumiwa, Jeinica Firginia (International Journal for Educational and Vocational Studies, 2020)
This study aims to describe the internalization of multicultural valuesfor students at Manado State University.  The diversity of Indonesian society is a rich gift of God. Therefore, this diversity must be managed properly in order to have a positive impact on the people of Indonesia. Differences should not be a reason for conflict in the community. One effort that can be done is to internalize multicultural valuesthrough the education process.This research uses a descriptive qualitative approach related to the process of internalizing multicultural valuesin Manado State University students, especially in the Faculty of Social Sciences as the object of research. Data obtained through observation, interviews and documentation, while data analysis is done by the process of presenting data, data reduction, and drawing conclusions. The results of this study indicate that the internalization of multicultural valuesis developed through learning activities in the classroom through Multicultural Education, Religious Education, and Valuesand Moral Education courses. In addition, the internalization of valuesis also carried out through student activities and interactions within the faculty and university environment.